Cover Feature: A New Phenanthroline Ligand and the Spontaneous Resolution of its Homoleptic Copper(I) Complex (Eur. J. Org. Chem. 47/2020). Issue 47 (6th November 2020) - Appleton, Jordan L.; Silber, Vincent; Karmazin, Lydia; Bailly, Corinne; Chambron, Jean‐Claude; Weiss, Jean; Ruppert, Romain
Abstract : The Cover Feature shows a new substitution pattern obtained when reacting phenanthrolines with organolithium compounds. Contrary to the now classical 2, 9‐disubstitution described in the seminal paper of Christiane Dietrich‐Buchecker et al., to whom this article is dedicated, a 2, 7‐disubstitution pattern was found by chance under given conditions. A rare spontaneous resolution of its bis(phenanthroline)copper(I) complex in the solid state is also described in the article. (cover picture created by Nina Hernandez). More information can be found in the Full Paper by R. Ruppert et al.